Ecodesign: Green Solutions for Design of Steel Building Envelopes - Di Ruocco, Giacomo; Frulio, Federica (International Journal of Architectural Engineering Technology, 2025)
In recent years, the impact that man has on the environment has become increasingly evident, and the planet itself is starting to re-bel against this great and uncontrolled exploitation of its resources. The need to seek change by approaching a totally sustainable lifestyle is now obvious. Sustainability has in fact become a major player in today's society, infiltrating every area of it, including construction. In the construction field, man's impact is unfortunately inevitable, but it can be mitigated by developing new sustainable technologies, and it is precisely with these that we have had the opportunity to approach a new vision of architecture, arriving at what is called Ecodesign, a way of designing that respects the environment and the resources offered by Nature. The research was conducted on a new building, under construction, within the university campus of Fisciano, Salerno, designed mainly with a steel construction system.